Cohesion and Coherence of News Discourse in Kompas.Com The Vice President Wants SMA 4 Sukabumi to Be an Example of Face-To-Face Learning in The Green Zone - Ilmiyatur Rosidah; Sugianti; Alfa Julia (CV. Inara, 2021)
The purpose of this research is to examine the cohesion and coherence of the news on Kompas.com entitled The Vice President Wants SMA 4 Sukabumi to Become a Face-to-Face Model in the Green Zone. This research was conducted to test the cohesion and coherence of a public reading. Where, the linguistic element is also a factor in the readability of information. One form or source of information can be obtained from the media. Some people use tools such as Facebook, Instagram, WhatsApp, and Kompas.com. The choice of Kompas.com media as a source of research data because Kompas.com is considered a trusted and accurate information medium, so many people often read and get information there. The method used in this research is descriptive research method. Data analysis was carried out by collecting data, describing the cohesion and coherence in the data, and entering it into the data analysis column. The results of this analysis process are the use of cohesion in the form of intra-sentence pronouns such as he, she, his, and so on. In addition to the form of conjunction in the form of intra-sentence pronouns, in the text there is a form of coherence. Coherence can be seen in the coherent form shown by the substitution form which refers to the previous sentence such as the phrase